PENEGAKAN HUKUM TINDAK PIDANA CYBER CRIME DALAM BENTUK PHISING DI INDONESIA - Triyanto (GEMA, 2023)
The development of information technology has changed the times, bringing more modern human progress. This development has an impact on the digitalization era in various fields. This has an impact on the birth of phishing crimes. Advances in information technology have provided many opportunities for cyber crime in the form of phishing. This article aims to write about law enforcement for cybercrime in the form of phishing. Considering that the crime of phishing is a crime that has only recently emerged due to the development of information technology. There is a need for efforts by the state to control phishing crimes so that they do not harm society. Moreover, phishing perpetrators are increasingly sophisticated in this era. This research method is normative juridical